Africa RISING: Promoting sustainable intensification in northern Ghana - Pye-Smith, Charlie (International Livestock Research Institute, 2013)
This short photofilm presents some aspects of the work of Africa RISING in Ghana. It shows how it is helping farmers restore their degraded lands, increase crop and livestock production, and provide them with better incomes.Photos and story by Charlie Pye-Smith. More at http://africa-rising.net